2022
DOI: 10.1371/journal.pone.0266380
|View full text |Cite
|
Sign up to set email alerts
|

Outreach screening to address demographic and economic barriers to diabetic retinopathy care in rural China

Abstract: Importance Poor access to existing care for diabetic retinopathy (DR) limits effectiveness of proven treatments. Objectives We examined whether outreach screening in rural China improves equity of access. Design, setting and participants We compared prevalence of female sex, age > = 65 years, primary education or below, and requiring referral care for DR between three cohorts with diabetes examined for DR in neighboring areas of Guangdong, China: passive case detection at secondary-level hospitals (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Socioeconomic deprivation is a major risk for nonattendance of DR screenings even in developed countries such as the United States of America, the United Kingdom, and Saudi Arabia [15]. Xiao et al suggested that DR outreach screenings in rural communities in China are more reliable in reaching women, older populations, and less-educated individuals compared to passive case detection in hospitals and referral centers [24]. Therefore, a mobile DR screening program is an effective strategy that could be adopted in PNG to meet the population demands and enhance the uptake of DR services.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic deprivation is a major risk for nonattendance of DR screenings even in developed countries such as the United States of America, the United Kingdom, and Saudi Arabia [15]. Xiao et al suggested that DR outreach screenings in rural communities in China are more reliable in reaching women, older populations, and less-educated individuals compared to passive case detection in hospitals and referral centers [24]. Therefore, a mobile DR screening program is an effective strategy that could be adopted in PNG to meet the population demands and enhance the uptake of DR services.…”
Section: Discussionmentioning
confidence: 99%